Hypothetical protein FoDbp40 influences the growth and virulence of Fusarium oxysporum by regulating the expression of isocitrate lyase - Zhao, Busi; He, Dan; Gao, Song; Zhang, Yan; Wang, Li (Frontiers in Microbiology, 2022)
Fungal growth is closely related to virulence. Finding the key genes and pathways that regulate growth can help elucidate the regulatory mechanisms of fungal growth and virulence in efforts to locate new drug targets. Fusarium oxysporum is an important plant pathogen and human opportunistic pathogen that has research value in agricultural and medicinal fields. A mutant of F. oxysporum with reduced growth was obtained by Agrobacterium tumefaciens-mediated transformation, the transferred DNA (T-DNA) interrupted gene in this mutant coded a hypothetical protein that we named FoDbp40. FoDbp40 has an unknown function, but we chose to explore its possible functions as it may play a role in fungal growth regulatory mechanisms. Results showed that F. oxysporum growth and virulence decreased after FoDbp40 deletion. FOXG_05529 (NCBI Gene ID, isocitrate lyase, ICL) was identified as a key gene that involved in the reduced growth of this mutant. Deletion of FoDbp40 results in a decrease of more than 80% in ICL expression and activity, succinate level, and energy level, plus a decrease in phosphorylated mammalian target of rapamycin level and an increase in phosphorylated 5′-adenosine monophosphate activated protein kinase level. In summary, our study found that the FoDbp40 regulates the expression of ICL at a transcriptional level and affects energy levels and downstream related pathways, thereby regulating the growth and virulence of F. oxysporum.